CAPN1 mutations broadening the hereditary spastic paraplegia/spinocerebellar ataxia phenotype. Issue 5 (20th April 2018) - Lambe, Jeffrey; Monaghan, Bernadette; Munteanu, Tudor; Redmond, Janice
Abstract : Increasing availability of next-generation sequencing technologies has revealed several limitations of diagnosis-driven traditional clinicogenetic disease classifications, particularly among patients with an atypical or mixed phenotype. Hereditary spastic paraplegia (HSP) and spinocerebellar ataxia (SCA) are two such disease entities with an often overlapping presentation, in which next generation exome sequencing has played a key role in identification of genes causing disease along a continuum of ataxia and spasticity. We describe a patient who presented with features of both ataxia and spasticity, in whom initial diagnostic testing was inconclusive. Ultimately next generation exome sequencing identified homozygosity for a pathogenic variant in exon 13 of the CAPN1 gene c.1534C>T(p.Arg512Cys). This case supports consideration of a less discriminatory classification system among such patients, potentially allowing for more expedient diagnosis through testing of a larger gene panel along the 'ataxia-spasticity spectrum'.